PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) BERBASIS SUMBERDAYA LOKAL UNTUK PENINGKATAN PENDAPATAN RUMAH TANGGA PETANI - Yadi heryadi; Betty Rofatin (Journal of Empowerment Community, 2020)
The problem of poverty alleviation of the population is remains a big homework for the Tasikmalaya District Government with 189,350 poor population in 2017 or around 10.84% of the total population of 1,806,775 people. Poverty requires real empowerment. In rural areas empowerment can be done at the Farmers Women's Group (KWT) which is a forum for women to take part in advancing the agricultural sector. KWT Sri Rahayu is a group that has long been a producer of salak fruit processing, but its business has not developed well because of various things including monotonous products, packaging and brands that are still simple so that marketing access is limited. Methods for agreed upon solutions include counseling, product diversification, packaging / brand handling training and assistance so that the products become a product that can be proud of and can increase the income and welfare of farmers' households in the region. The results of activities have been able to increase competitiveness, value added products and alternative processed Salak products and improvement of community values. The conclusion is that the problems faced by KWT Sri Rahayu can be overcome well, although not yet optimal.Â Â